A 3D numerical model to Track Marine Plastic Debris (TrackMPD): Sensitivity of microplastic trajectories and fates to particle dynamical properties and physical processes. (April 2019) - Jalón-Rojas, Isabel; Wang, Xiao Hua; Fredj, Erick
Abstract: Numerical modelling is a key tool in understanding and determining the sources, trajectories and fates of micro-plastic debris (MPD). In this study, we introduce TrackMPD, a new modelling framework for the 3D transport of marine debris. TrackMPD fills the gaps in previous models by: (1) using a three-dimensional approach; (2) providing compatibility with a variety of ocean models; and (3) including a wide range of physical processes (advection, dispersion, windage, sinking, settling, beaching and re-floating) and MPD behaviours that depend on particle dynamical properties, and the fouling and degradation states. We implement a sensitivity analysis based on 44 scenarios to assess the relative importance of the different processes and behaviours on the MPD trajectories and fates. Results show that the MPD dynamical properties that impact their sinking, in particular plastic density and biofilm thickness and density, have the biggest effect on the MPD transport, followed by turbulent dispersion and washing-off. Graphical abstract: Unlabelled Image Highlights: Novel three-dimensional approach for modelling marine plastic debris transport Innovative modelling of physical processes and behaviour of microplastics High influence of vertical current shear on the dispersion of microplastics High impact of density and biofouling on sinking, and thus on trajectories and fates Particle size impacts the trajectories of spherical particles, but not of cylindrical.